The Effect of Feed and Gonadotrophin Hormone on The Litter Size and Birth Weight of Local Goat - Sugijatno, Sugijatno (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2003)
A study was conducted to determine the effect of ration and gonadotrophin hormone on the reproductive performance of breeding goat. Twenty-three does and six bucks having a similar age (1.5-2.0 years old) were exposed in this experiment. An amount of 200 gram of concentrate consisting of yellow corn (30%), rice brand (50%) and commercial concentrate CP 235 (20%) has been given to each experimental animal. The experimental animals were divided into two groups. The group was fed (12 animals) with M1 (roughage + concentrate) and the other group was fed (11 animals) with M2 (roughage). Moreover, each group were divided into four treatment namely: T1 (PGF2Î±), T2 (PGF2Î± + PMSG), T3 (PGF2Î± + HCG) and T4 (PGF2Î± + PMSG + HCG). The same treatment was applied to the other group. The data such as litter size and birth weight were collected from each experimental goat. Those data were analyzed using a 2 x 4 factorial experiment with unequal repetition. A composition between to treatment group was done using Least Significant Design (LSD). The result of the study showed that the effect of ration and gonadotrophin hormone on litter size and birth weight didnât show any significant difference (P>0.05). The average of litter size and birth weight from roughage + concentrate treated animal (goat) were 1.92 and 1.51 kilogram respectively. However, the average of litter size and birth weight from roughage treated group were 1.58 and 1.48 kilogram respectively. (Animal Production 5(1): 5-10 (2003)Â Key words : Gonadotrophin, PGF2Î±, PMSG, Hormone, Goat